Revolutionizing the Future: The Importance of Utilizing Food Technology for Sustainable Nutrition and Global Prosperity - Megavitry, Rissa; Harahap, Rahma Hayati (Westscience Press, 2023)
In the face of escalating global challenges stemming from population growth, climate change, and resource depletion, the imperative to devise sustainable solutions for food production and nutrition has become paramount. This research delves into the pivotal role of food technology in reshaping the future of nutrition and fostering global prosperity. Through an exhaustive review of existing literature, examination of current technological trends, and an exploration of potential future developments, the study aims to elucidate the methods and strategies that can be employed to harness food technology for sustainable nutrition. By comprehending the challenges and opportunities within this sphere, we endeavor to pave the way for a more secure, nutritious, and prosperous global food system.